2012
DOI: 10.1007/s00285-012-0506-0
|View full text |Cite
|
Sign up to set email alerts
|

Limitations of perturbative techniques in the analysis of rhythms and oscillations

Abstract: Perturbation theory is an important tool in the analysis of oscillators and their response to external stimuli. It is predicated on the assumption that the perturbations in question are "sufficiently weak", an assumption that is not always valid when perturbative methods are applied. In this paper, we identify a number of concrete dynamical scenarios in which a standard perturbative technique, based on the infinitesimal phase response curve (PRC), is shown to give different predictions than the full model. She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 42 publications
0
20
1
Order By: Relevance
“…This is in contrast to high sensitivity to initial conditions usually reported in neuron models with an external input (e.g. shear-induced chaos in the periodically kicked Morris-Lecar neuron [15]). [4,5], which corresponds to the quiescent segment on the limit cycle.…”
Section: Application To Bursting Neuronscontrasting
confidence: 74%
“…This is in contrast to high sensitivity to initial conditions usually reported in neuron models with an external input (e.g. shear-induced chaos in the periodically kicked Morris-Lecar neuron [15]). [4,5], which corresponds to the quiescent segment on the limit cycle.…”
Section: Application To Bursting Neuronscontrasting
confidence: 74%
“…There it was shown that a combined phase and amplitude analysis is needed to completely describe the phenomenon. In addition, [51] explores scenarios where geometry and phase-space structures play a critical role, so that perturbative approaches based on phase response curves can not predict the dynamical behavior. Since the approach of [19] does not apply to full spiking induced by noise, a corresponding theory is still needed for such a case.…”
Section: Discussionmentioning
confidence: 99%
“…This space is assumed to be a finite dimensional compact manifold. The advantages of considering that dim(x i ) ≥ 1 (not necessarily 1) are, among others, the possibility of showing dynamical bifurcations between different rythms and oscillations that appear in some biological neurons [10], that would not appear if the mathematical model of all the neurons were necessarily one-dimensional.…”
Section: Model Of An Isolated Neuronmentioning
confidence: 99%